PENGARUH STRUKTUR MODAL DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022–2024) - Rizka Ardillah; Riska Ayu Setiawati (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of Capital Structure and Good Corporate Governance (GCG) on the financial performance of banks listed on the Indonesia Stock Exchange for the period 2022–2024. Capital Structure is measured by the Debt to Equity Ratio (DER), while GCG is represented by the Board of Commissioners, Board of Directors, Audit Committee, and Institutional Ownership. Financial performance is measured using Return on Assets (ROA). The analysis was conducted using multiple linear regression with SPSS version 27. The results show that Capital Structure has a significant effect on financial performance, while all GCG indicators do not have a significant partial effect. However, simultaneously, all independent variables have a significant effect on financial performance. These findings indicate that optimal management of Debt to Equity Ratio (DER) in accordance with regulatory provisions is an important factor in maintaining the stability of bank profitability. In addition, the effective implementation of GCG through increased board competence and independence is necessary to strengthen oversight and transparency. The results of this study have practical implications for bank management and investors in making funding decisions, governance policies, and strategies to improve financial performance